Evaluation of reversed-phase thin layer chromatographic protocol to detect vegetable oil/fat in milk - ., Sukthija; Sharma, Vivek; Arora, Sumit; Singh, Richa; Raju, P N; H V, Raghu (Indian Journal of Dairy Science, 2019)
Adulteration of milk fat in raw milk with vegetable oil/ fats with pre-adjusted BR- reading, Reichert Meissl and Polenske values is becoming a common practice in the present scenario of rampant adulteration of milk and milk products. Detection of such type of adulteration using traditional or routine methods wherein physico-chemical constants of milk fat are used as a basis becomes impossible and continues to be a challenge for the dairy industry. Hence, in the present study, relatively rapid and convenient protocol based on Reversed-phase thin layer chromatographic was developed to check the purity of milk fat in milk. Using the Reversed- phase thin layer chromatographic protocol the added adulterant oils (rice bran oil, soybean oil, sunflower oil and groundnut oil) in milk could be detected to the minimum level of 1%.Â Â